Drug delivery: enabling technology for drug discovery and development. iPRECIO® Micro Infusion Pump: Programmable, refillable and implantable - Tan, Tsung; Watts, Stephanie W.; Davis, Robert P. (Frontiers in Pharmacology, 2011)
Successful drug delivery using implantable pumps may be found in over 12,500 published articles. Their versatility in delivering continuous infusion, intermittent or complex infusion protocols acutely or chronically has made them ubiquitous in drug discovery and basic research. The recent availability of iPRECIO®, a programmable, refillable and implantable infusion pump has made it possible to carry out quantitative pharmacology (PKPD) in single animals. When combined with specialized catheters, specific administration sites have been selected. When combined with radiotelemetry, the physiologic gold standard, more sensitive and powerful means of detecting drug induced therapeutic and/or adverse effects has been possible. Numerous application examples are cited from iPRECIO® use in Japan, United States and Europe with iPRECIO® as an enabling drug delivery device where the refillable and programmability functionality were key benefits. The ability to start/stop drug delivery and to have control periods prior dosing made it possible to have equivalent effects at a much lower dose than previously studied. Five different iPRECIO® applications are described in detail with references to the original work where the implantable, refillable and programmable benefits are demonstrated with their different end-points.